The effects of hydrogen sorption on the resistance and work-function of titanium films at 290K - Kandasamy, K.; Surplice, N.A. (Elsevier B.V., 1984)
Ti films readily sorbed hydrogen up to an atomic ratio r=2.0 at a saturation pressure of 2*10-3 Torr. The turning points on the curve of resistance R versus r were correlated with the phase boundaries. The maximum on this curve agreed well with the data of Wedler and Strothenk (1966), and gave the solubility limit for H in Ti films at 290K as H/Ti=0.07. The data for the work-function phi agreed fairly well with Magee's (1968). The phi curve showed that the Fermi level mu of the FCC hydride was 0.14 eV higher than mu of the FCT phase, and at least 0.28 eV lower than mu for the clean metal. These data are compared briefly with the results of modern calculations on the band structure. The FCC/FCT phase boundary was at r=1.8 at 20 degrees C and r approximately=1.85 at 50 degrees C, and the FCC/FCT transition temperature was >50 degrees C.